Wunderlich syndrome as the first manifestation of an extraskeletal Ewing sarcoma - Kim, Jong Wook (Can Urol Assoc J, 2015)
We recently encountered an extremely rare case of spontaneous perirenal hemorrhage in a 34-year-old man. He initially had undergone radical nephrectomy owing to suspicion of renal cell carcinoma. The final diagnosis was extraskeletal Ewing sarcoma.